Prevalence of black tooth stains and dental caries in Brazilian schoolchildren - Gasparetto André; Conrado Carlos Alberto; Maciel Sandra Mara; Miyamoto Ernesto Yiokihiro; Chicarelli Mariliane; Zanata Régia Luzia (Fundação Odontológica de Ribeirão Preto, 2003)
This study evaluated the correlation between the presence of black extrinsic tooth stains and caries in Brazilian schoolchildren. The target population consisted of 263 children aged 6-12 years. Clinical examinations were performed by four dentists calibrated for the World Health Organization criteria for caries diagnosis. The c² test was used to compare the prevalence of caries between groups of children with and without black tooth stains. Spearman's correlation test was used to analyze the relationship between the presence of black stains and caries severity. Black stains were observed in 14.8% of the children. The number of children with caries-free permanent dentition was not statistically different between groups. The mean DMF-T was 1.46 ± 1.39 for children with black stains and 2.42 ± 2.09 for children without black stains. A negative correlation was observed between the presence (r = -0.16; p<0.05) and severity (r = -0.15; p<0.01) of black stains and DMF-T.